Transnational Islamic Bioethics: A Comparative Study of Sharia-Based Approaches to Genetic Editing and Global Medical Ethics - Wawan Juandi; Nahe'i Nahe'i; Muhyiddin Khotib (International Forum of Researchers and Lecturers, 2024)
This study explores the ethical perspectives of genetic editing from two distinct frameworks: Islamic bioethics and global medical ethics. Both ethical systems emphasize the protection of human dignity and the prevention of harm, aligning with the broader goal of promoting health. However, significant differences emerge when addressing the issue of genetic editing, particularly in relation to human procreation. While global bioethics focuses on universal human rights, Islamic bioethics introduces religious principles rooted in Sharia law, such as Maqasid al-Sharia (objectives of Sharia) and Maslahah (public interest), to guide the ethical evaluation of genetic technologies. The findings reveal that while both frameworks agree on the importance of medical necessity, the treatment-enhancement distinction plays a critical role in Islamic perspectives, leading to more cautious stances on genetic modifications aimed at enhancing non-medical traits. The study also underscores the cultural and regional variations in Islamic bioethics, reflecting how different Islamic schools of thought impact fatwa decisions on genetic editing. In comparison, global bioethics aims to establish universal principles, often focusing on human rights, equality, and equity. The paper concludes by recommending more inclusive discussions between Islamic scholars and global bioethicists to bridge the gap between religious ethics and global standards. This would help ensure that genetic technologies are applied ethically, respecting both cultural values and universal human rights, and addressing the challenges posed by emerging genetic technologies.